Using sensor technology to track performance in para XC skiing: time well spent or time wasted? - Baumgart, J. K.; Carlsen, C. H.; Kocbach, J.; Severin, C.; Sandbakk, O. (Nordic Winter Sports Conference, 2020)
Para cross-country (XC) skiers are divided into three categories for each sex (physically impaired sitting and standing, visually impaired standing) where a time factor is used to adjust for disability-related performance differences within each category. Despite the use of this time factor, differences between the first three ranks are often larger in Para XC skiers compared to able-bodied XC skiers (e.g. ~0.5-14% versus ~0.5-2% during the middle-distance races at the 2010-2018 Olympic/Paralympic Games). In able-bodied XC skiers, sensor technology with accompanying algorithms are increasingly used to track speed and investigate mechanisms related to won or lost time, such as choice of and transitions between sub-techniques and inherent cycle kinematics. In a sitting Para XC skier, a slightly modified algorithm was used to investigate the differences in speed between low intensity (LIT) and high intensity skiing (HIT). The higher speed during HIT was mainly due to an increased cycle rate (60-61 versus 45-55 cycles·min-1), whereas cycle length was longer only in uphill terrain (3.0 versus 2.6 m). Furthermore, preliminary analyses showed a large time loss for a LW4 skier compared to an able bodied XC skier (~25 sec) especially in the uphill terrain. This was associated with almost twice as many time-consuming sub-technique transitions (16 vs. 9, respectively), particularly between the diagonal stride and kick double poling technique. We speculate that this is related to individual preference, lower speed and/or reduced joint mobility and muscle mass in the left leg of this particular LW4 skier. Overall, these two examples highlight the benefits of, and justify the time spent on these analyses, since we contribute to an increased understanding of Para XC skiing performance. However, further research is required to see whether these methods can distinguish performance differences in specific terrains, sub-techniques or kinematic patterns related to the type and extent of disability - and thereby improve the classification system. Such research requires larger samples of athletes, collected through collaborations between international research institutions while communicating closely with the International Paralympic Committee, sport governing bodies, coaches and athletes.